2022
DOI: 10.3390/ani12212993
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Acute Phase Response Biomarkers in Racing Endurance Horses

Abstract: This study aimed to evaluate if exercise-induced acute phase response (APR) occurs in endurance horses in response to the race. The study included 23 horses competing in an endurance competition with a successfully passed clinical examination before the race. Blood samples were collected before the start and within 30 min after the end of the race. Haematological and biochemical tests were performed and correlated to acute phase biomarkers changes. Values of calprotectin and haptoglobin (Hp) decreased after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, when considering the plasma shift–adjusted values, it becomes clear that the alleged increase is in fact much smaller and has no relevance. Haemolysis after exercise can be caused by mechanical damage to the erythrocytes or a low oxygen content during exercise and is also suspected in endurance horses (Mihelic et al., 2022). Mechanically induced or cytokine‐induced cell damage in the form of an inflammatory reaction in the musculature (Nieman et al., 2005; Smith, 2000) could be the cause of the observed signs of haemolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when considering the plasma shift–adjusted values, it becomes clear that the alleged increase is in fact much smaller and has no relevance. Haemolysis after exercise can be caused by mechanical damage to the erythrocytes or a low oxygen content during exercise and is also suspected in endurance horses (Mihelic et al., 2022). Mechanically induced or cytokine‐induced cell damage in the form of an inflammatory reaction in the musculature (Nieman et al., 2005; Smith, 2000) could be the cause of the observed signs of haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that there is an exercise‐induced increase in liver enzymes without liver disease (McGowan 2008). In endurance horses, the increase in GGT is not as big, but the increase in AST is even bigger than in eventing horses (Mihelic et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In horses, the CRP is a moderate APP and an increase in its concentration has been reported after castration, in enteritis, arthritis, laminitis and induced inflammation [9]. A reaction analogous to the APR in inflammatory conditions has also been reported after exercise in humans [10,11] and in athletic horses [12,13]. As a matter of fact, physical exercise induces various stress responses and metabolic adaptations.…”
Section: Introductionmentioning
confidence: 95%